The fates of the circumgalactic medium in the FIRE simulations. Issue 3 (9th April 2020) - Hafen, Zachary; Faucher-Giguère, Claude-André; Anglés-Alcázar, Daniel; Stern, Jonathan; Kereš, Dušan; Esmerian, Clarke; Wetzel, Andrew; El-Badry, Kareem; Chan, T K; Murray, Norman
ABSTRACT: We analyse the different fates of the circumgalactic medium (CGM) in FIRE-2 cosmological simulations, focusing on the redshifts z  = 0.25 and 2 representative of recent surveys. Our analysis includes 21 zoom-in simulations covering the halo mass range $M_{\rm h}(z=0) \sim 10^{10} \!-\! 10^{12} \rm {\, M}_\odot$ . We analyse both where the gas ends up after first leaving the CGM (its 'proximate' fate) and its location at z  = 0 (its 'ultimate' fate). Of the CGM at z  = 2, about half is found in the ISM or stars of the central galaxy by z  = 0 in M h ( z  = 2) ∼ 5 × 10 11 M⊙ haloes, but most of the CGM in lower mass haloes ends up in the intergalactic medium (IGM). This is so even though most of the CGM in M h ( z  = 2) ∼ 5 × 10 10 M⊙ haloes first accretes on to the central galaxy before being ejected into the IGM. On the other hand, most of the CGM mass at z  = 0.25 remains in the CGM by z  = 0 at all halo masses analysed. Of the CGM gas that subsequently accretes on to the central galaxy in the progenitors of M h ( z  = 0) ∼ 10 12 M⊙ haloes, most of it is cool ( T ∼ 10 4 K) at z  = 2 but hot (∼ T vir ) at z ∼ 0.25, consistent with the expected transition from cold mode to hot mode accretion. Despite the transition in accretion mode, at both z  = 0.25 and $2 \, {\gtrsim} 80{{\ \rm per\ cent}}$ of the cool gas in $M_{\rm h} \gtrsim 10^{11} \rm {M}_\odot$ haloes will accrete on to a galaxy. We find that the metallicity of CGM gas is typically a poor predictor of both its proximate and ultimate fates. This is because there is in general little correlation between the origin of CGM gas and its fate owing to substantial mixing while in the CGM.